Impact of packaging material and storage condition on retention of provitamin A carotenoids and xanthophylls in yellow-seeded maize flour - Awoyale, W.; Alamu, Emmanuel Oladeji; Irondi, E.A.; Maziya-Dixon, Busie; Menkir, A. (Functional Food Center, 2018)
Background: Pro-vitamin A carotenoid (pVAC) rich foods are those foods that contain substance which can be converted within the human body into retinol. These foods also contribute to the reduction of vitamin A deficiency diseases. Yellow-seeded maize flour is a pVAC rich food. Identifying the right packaging materials and storage conditions that retain pVAC in this food is essential for their health benefits. Traditionally, maize flour is stored with different packaging materials to increase its shelf life. For example, previous studies have shown how during storage in different food matrices, carotenoids, including maize grains, are highly susceptible to degradation by temperature, light, and oxygen. Therefore, in this study we investigated the effect of storage packaging materials (polypropylene woven sacks-PWS, high-density polyethylene bags-HDPE, and polyvinyl plastic containers-PPC) and storage condition (temperature and relative humidity) on retaining pVAC in yellow-seed maize flour.